2020
DOI: 10.1038/s41598-020-59333-4
|View full text |Cite
|
Sign up to set email alerts
|

Record statistics of bursts signals the onset of acceleration towards failure

Abstract: Forecasting the imminent catastrophic failure has a high importance for a large variety of systems from the collapse of engineering constructions, through the emergence of landslides and earthquakes, to volcanic eruptions. Failure forecast methods predict the lifetime of the system based on the time-to-failure power law of observables describing the final acceleration towards failure. We show that the statistics of records of the event series of breaking bursts, accompanying the failure process, provides a pow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…A combination of these early warning signals was found to be the best approach to develop a reliable alarm system for structural collapse. Recently, a fiber bundle model has shown that the statistics of records of the event series of breaking bursts provide a very good tool to detect the acceleration breaking bursts, which could be used as an early warning of an imminent catastrophic failure [63]. Similar results have also been reported during soft uniaxial compression of three silica-based (SiO 2 ) nanoporous materials.…”
Section: Collapse Predictingsupporting
confidence: 54%
“…A combination of these early warning signals was found to be the best approach to develop a reliable alarm system for structural collapse. Recently, a fiber bundle model has shown that the statistics of records of the event series of breaking bursts provide a very good tool to detect the acceleration breaking bursts, which could be used as an early warning of an imminent catastrophic failure [63]. Similar results have also been reported during soft uniaxial compression of three silica-based (SiO 2 ) nanoporous materials.…”
Section: Collapse Predictingsupporting
confidence: 54%
“…Such behavior indicates critical dynamics, particularly selforganized critical dynamics for the system, where the universality hypothesis is still applicable, without having to fine-tune a driving parameter [7]. Such a phenomenon is therefore open for analysis with the tools of critical phase transitions, universality and therefore is an important step toward predictability of imminent failure [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The avalanche statistics as well as the effect of system sizes has also been discussed recently in the context of fiber bundle model [49,50]. Moreover, the record statistics in the avalanche statistics and study of elastic energy has been observed to be a vital key to predicting an upcoming failure [51]. The occurrence of different regimes with increasing disorder strength is also observed in spin systems as well.…”
Section: Introductionmentioning
confidence: 97%